The dual role of empathy in clinical trial decisions - Chichua, Mariam; Filipponi, Chiara; Mazzoni, Davide; Marinucci, Marco; Masiero, Marianna; Pravettoni, Gabriella (Frontiers in Psychology, 2025)
IntroductionEmpathy is a key driver of prosocial behaviors, including motivations to participate in clinical trials. Our study aimed to explore how individuals’ levels of empathy influence their intention to participate in a trial, examining scenarios where participants envision the decision for themselves (Condition 1 - “Self”) and when they consider a hypothetical person (Condition 2 - "Other”), who has to take that decision.MethodsA between-subject design was conducted on 176 healthy participants (Mage = 31.98, SD = 10.14). All participants responded to socio-demographic questions and were assessed for empathy. They were randomly assigned to two conditions presenting a hypothetical cancer clinical trial and assessing the intention to partake in the trial.ResultsThe moderation regression model was statistically significant [R2 = 0.10, F(7,167) = 2.04, p < 0.05]. Simple slopes analysis showed that for Condition 1, each unit increase in empathy was associated with 8.59 unit increase in intention to partake in a clinical trial [b = 8.59, SE = 4.04, 95% CI: 0.61, 16.6], whereas for Condition 2 each unit increase in empathy was associated with −9.77 unit decrease in intention [b = −9.77, SE = 3.78, 95% CI:−17.24, −2.3]. The slope of empathy on intention for condition 1 was significantly different than for condition 2 [Δ = 18.4, SE = 5.5, t (167) = 3.34, p < 0.001].DiscussionEmpathy acts as a facilitator for partaking in trials when imagining having been diagnosed with cancer, while it becomes a barrier when thinking about another person’s participation. The reversed effect of empathy on intention shown in this study may guide future research and healthcare providers to discuss further before enrolment, involving both patients and caregivers in the decision-making process.